Flying from Europe to the Algarve: The Geographical Impacts of the Growth of Low-Cost Carriers (1996–2013) - Ramos-Pérez, David; Izquierdo-Misiego, José Ignacio (Journal of Tourism, Sustainability and Well-being, 2015)
The replacement of non-scheduled traffic by scheduled services is one of the main impacts that the liberalisation of the European Common Aviation Area has had on tourist airports. In the case of Faro, between 1996 and 2013, this shift led to both fewer routes served and reduced catchment areas in the source markets for tourists visiting the Algarve. The strategy pursued by Ryanair, the airport’s main carrier, focuses on connections that already channelled a greater volume of traffic when charter airlines dominated. Therefore, the impact of low-cost carriers on diversifying the number of airports of origin and source markets is limited. Moreover, using the spatial analysis functions of GIS software, we verified that the population linked to the theoretical catchment areas of airports with a non-stop flight to Faro in 2013 was smaller than that of the airports with such connections in 2000. The decision-making process involved in the policy incentives for introducing new routes could benefit greatly from this type of analysis.